2020
DOI: 10.1620/tjem.252.85
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Mediated Vasodilation and Reactive Hyperemia Index in Heart Failure with Reduced or Preserved Ejection Fraction

Abstract: Vascular endothelial dysfunction is part of the underlying pathophysiology of heart failure. However, there are no reports in which vascular endothelial function of both conduit arteries and microvasculature was assessed in patients with heart failure. This study was aimed to assess vascular endothelial function separately in heart failure with reduced (HFrEF) and preserved ejection fraction (HFpEF). We performed simultaneous measurement of both flow-mediated vasodilation for endothelial function of conduit ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Several studies reported a lower hyperaemic response after 5 min occlusion of the brachial vasculature in HFpEF patients compared to matched control subjects [ 24 , 26 , 28 , 29 ], which was associated with worse outcome [ 25 ]. However, HFpEF patients showed a better digital hyperaemic response than HFrEF patients [ 27 ]. Impaired endothelium-independent vasodilation was also shown in the forearm skin in coronary artery disease patients with HFpEF compared with patients without HF [ 11 ].…”
Section: Evidence Of Microvascular Dysfunction In Hfpefmentioning
confidence: 99%
“…Several studies reported a lower hyperaemic response after 5 min occlusion of the brachial vasculature in HFpEF patients compared to matched control subjects [ 24 , 26 , 28 , 29 ], which was associated with worse outcome [ 25 ]. However, HFpEF patients showed a better digital hyperaemic response than HFrEF patients [ 27 ]. Impaired endothelium-independent vasodilation was also shown in the forearm skin in coronary artery disease patients with HFpEF compared with patients without HF [ 11 ].…”
Section: Evidence Of Microvascular Dysfunction In Hfpefmentioning
confidence: 99%
“…In contrast, in non-ischaemic patients, the degree of FMD was lower in HFpEF patients compared to HFrEF patients (p = 0.009), whereas the RHI was similar in the two groups. These results suggest that the clinical significance of FMD and RHI measurements in patients with HF may diverge depending on the concomitant presence of coronary disease, rather than on the HF phenotype based on EF [56].…”
Section: Evidence Of Endothelial Dysfunction In Heart Failure With Pr...mentioning
confidence: 88%
“…Therefore, it is necessary to further explore the effect of dulaglutide on peripheral blood EPCs and arterial elasticity in non-obese T2DM patients or T2DM patients with ASCVD. (3) Reactive hyperaemia index (RHI) and flow-mediated vasodilation (FDM) are valuable indexes to evaluate vascular endothelial function and predict the prognosis of cardiovascular disease [ 56 ]. Due to conditional limitations, we did not measure RHI and FDM while determining baPWV in subjects.…”
Section: Discussionmentioning
confidence: 99%